Pope's Chapel Annual Homecoming, October 6, 1974 - (:unkn) unknown (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Pope's Chapel Annual Homecoming, October 6, 1974. Harold Lawrence, pastor. Event program. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19741006.pdf. 4 pages. 36137827 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Bamford, John; Bohler, Clarence; Boyd, E. F.; Boyd, John W.; Bufford, Pearl; Butler, Carolyn; Chafin, Elizabeth; Combs, Farmer; Fortson, Benjamin Wynn; Hobbs, Arthur J.; Jones, Lester; Lawrence, Harold; Luther, Martin; Norman, Jimmy; Roberson, A. L.; Roberson, Pat; Roper, Sybil S.; Sale, David; Satterfield, Walker; Truitt, Horace; Walton, Jack; Wesley, John; Wiggins, Dixie; Wiggins, Tom B.